PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN MACROMEDIA FLASH CS 6 TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATERI SISTEM PEREDARAN DARAH MANUSIA - Zusette Ruslinda Wamiau (Jurnal Pendidikan Sains Universitas Muhammadiyah Semarang, 2019)
This study aims to determine the effect of the application of Macromedia Flash CS 6 learning media on students' cognitive learning outcomes in human circulatory system material and to know the implementation of Macromedia Flash CS 6 learning media on students' cognitive learning outcomes in class VIII human circulatory system in Christian Middle School 2 Salatiga. The method used in this study is quasi-experimental research. Based on the results of the study, the posttest results showed an average value of 78.4 which means reaching the KKM value standard of 75. While the ANOVA test shows that the Sig.value.> α which is 0.00> 0.05, which means that there are differences in the macromedia flash CS 6 learning media on students' cognitive learning outcomes in class VIII human circulatory system material in Christian Middle School 2 Salatiga.